The Effect of Tax Knowledge, Personality, Religiosity, Service Quality, and Tax Awareness on Individual Tax Compliance - Primandita Fitriandi (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2025)
Purpose: This research aims to examine and analyse the influence of individual and institutional factors on the tax compliance of individual taxpayers in Indonesia. Specifically, the study investigates the role of tax knowledge, personality traits, religiosity, service quality, and tax awareness in shaping compliance behaviour. Methodology: The research employs a quantitative approach using a structured survey method. Data were collected from 324 respondents selected through purposive sampling across Indonesia. Data analysis was conducted using Structural Equation Modelling with Partial Least Squares (SEM-PLS) technique to evaluate the hypothesised relationships among the variables. Findings: The findings indicate that tax knowledge, personality traits (particularly responsibility and discipline), the quality of fiscal services, and tax awareness have a positive and significant impact on tax compliance. However, religiosity does not demonstrate a statistically significant influence on compliance, suggesting that moral or spiritual values do not always correlate directly with fiscal responsibility in this context. Implication: These findings provide insights for policymakers regarding the importance of enhancing tax education and the quality of institutional services as strategies to encourage voluntary compliance. More effective strategies involve simplifying information and providing professional services rather than solely relying on ethical or moral approaches. Originality: This research integrates psychological (personality), sociological (religiosity), and institutional (service quality) factors simultaneously to provide a comprehensive overview of taxpayer behaviour in Indonesia. The study also highlights a gap between symbolic religiosity and actual behaviour in tax compliance within the local context.